2020
DOI: 10.1007/s10456-020-09753-7
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular dysfunction in COVID-19: the MYSTIC study

Abstract: Rationale Pre-clinical and autopsy studies have fueled the hypothesis that a dysregulated vascular endothelium might play a central role in the pathogenesis of ARDS and multi-organ failure in COVID-19. Objectives To comprehensively characterize and quantify microvascular alterations in patients with COVID-19. Methods Hospitalized adult patients with moderate-to-severe or critical COVID-19 (n = 23) were enrolled non-consecutively in this prospective, observational, cross-sectional, multi-center study. Fift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
264
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(308 citation statements)
references
References 41 publications
22
264
0
8
Order By: Relevance
“…Indeed, contrary to our results, Edul et al ( 9 ) showed a decline in RBC velocity accompanied by an increase in vessel density in patients suffering from Covid-19 pneumonia. Furthermore, Rovas et al ( 10 ) noted reductions in RBC velocity with decreases in vessel density in this cohort. Since hypoxemia induces both capillary recruitment and angiogenesis ( 9 ), differences might be related to the higher compromise of pulmonary oxygenation in our patient [PaO 2 /FiO 2 ratio, 112.5 mmHg vs. 122 ± 43 mmHg ( 9 ) vs. 194.88 (145.76–234.0) mmHg ( 10 )].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Indeed, contrary to our results, Edul et al ( 9 ) showed a decline in RBC velocity accompanied by an increase in vessel density in patients suffering from Covid-19 pneumonia. Furthermore, Rovas et al ( 10 ) noted reductions in RBC velocity with decreases in vessel density in this cohort. Since hypoxemia induces both capillary recruitment and angiogenesis ( 9 ), differences might be related to the higher compromise of pulmonary oxygenation in our patient [PaO 2 /FiO 2 ratio, 112.5 mmHg vs. 122 ± 43 mmHg ( 9 ) vs. 194.88 (145.76–234.0) mmHg ( 10 )].…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, Rovas et al ( 10 ) noted reductions in RBC velocity with decreases in vessel density in this cohort. Since hypoxemia induces both capillary recruitment and angiogenesis ( 9 ), differences might be related to the higher compromise of pulmonary oxygenation in our patient [PaO 2 /FiO 2 ratio, 112.5 mmHg vs. 122 ± 43 mmHg ( 9 ) vs. 194.88 (145.76–234.0) mmHg ( 10 )]. Spontaneous pneumomediastinum associated with Covid-19 has occasionally been reported ( 11 ).…”
Section: Discussionsupporting
confidence: 58%
“…As shown in Table 2 , a total of 16 studies were included for the title and abstract screening, and 2 studies were excluded due to duplicates. After a total of 11 studies were not deemed eligible for full-text review, 6 reports [ 3 , 87 , 88 , 89 , 90 , 91 ] were included in the review. Figure 14 presents a flowchart depicting the selection process.…”
Section: Literature Search Results For Veglx In Covid-19mentioning
confidence: 99%
“…On the other hand, the vascular endothelial glycocalyx (VEGLX), the extracellular matrix covering vascular endothelial cells throughout the body, is also impaired by various risk factors, and there have been numerous reports of VEGLX damage in acute respiratory distress syndrome (ARDS) and disseminated intravascular coagulation (DIC), which may be closely related to vascular endothelial damage in severe COVID-19. Recently, circulating levels of fragmented VEGLX concentrations and real-time measurements of VEGLX in sublingual capillaries have been reported in patients with COVID-19 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID‐19) is an infectious disease caused by severe acute respiratory coronavirus 2 (SARS‐CoV‐2). Among hospitalized patients, many have developed typical manifestations of sepsis‐like cold extremities, weak peripheral pulses or severe metabolic acidosis, indicating microcirculation dysfunction 1 . Microvascular dysfunction has been reported in sepsis 2,3 and could be partly caused by red blood cell (RBC) rheological alterations such as decreased RBC deformability (RBCD), 4 increased RBC aggregation 5 and abnormal RBC morphology/physiology 6 .…”
mentioning
confidence: 99%